Cutaneous Adverse Reactions to TNF Alpha Blockers. Case Report and Literature Review - Alina DUMITRU; Catalin DUMITRASCU; Ana DUMITRACHE; Cristina ALEXANDRU; Anca FLORESCU; Carmen IORGUS; Florin Teodor BOBIRCA; George CIOBOTARU; Ioan ANCUTA; Anca BOBIRCA (Modern Medicine)
Biological therapy is used in a wide range of medical settings. Adverse reactions to biological therapy can limit their widespread use, so early detection and treatment can adjust attempts to stop these molecules. TNF Alpha blockers may cause the following skin reactions in alpha patients: injection site reactions, infections, immune-mediated reactions (psoriasis, psoriasis, drug-induced lupus, vasculitis, hidradenitis, alopecia), allergic or neoplastic reactions. We present the case of a patient with RA who developed skin lesions during biological therapy and was diagnosed with drug-induced lupus based on clinical elements, associated autoimmunity, and dermatological evaluation. The skin lesions were attributed to the interaction of three medications (biosimilar Etanercept, Leflunomide, and Isoniazid), all of which have been implicated in causing these side effects. The solutions that saved the patient were temporarily discontinuing the immunosuppressive medication and replacing it with a local corticoid, followed by the continuation of Etanercept in associated with Methotrexate, and the patient was able to continue the biological medication and obtain a favorable response to the treatment. In conclusion, skin changes caused by TNF Alpha inhibitors are common, but vary in severity, and do not warrant therapy interruption.